2008
DOI: 10.1002/pds.1609
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension management in diabetic patients: prescribing trends from 1999 to 2005 in three Japanese university hospitals

Abstract: The rapid increase in use of ARBs and under-use of thiazides may be explained by the fee schedule in the Japanese health insurance system. The paucity of large-scale clinical trials may also hinder evaluation of the traditional view of the role of beta-blockers and thiazides in treatment of Japanese patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We were unable to identify any previous studies that evaluated antihypertensive prescribing rates across a patient population classified by comorbidity type, although two studies assessed drugs prescribed to the specific subpopulation of hypertensive patients with diabetes mellitus (19,20). Whereas diabetes mellitus is a compelling indication for use of RAS inhibitors (2), we found that CCBs are still commonly prescribed in this subgroup.…”
Section: Discussionmentioning
confidence: 89%
“…We were unable to identify any previous studies that evaluated antihypertensive prescribing rates across a patient population classified by comorbidity type, although two studies assessed drugs prescribed to the specific subpopulation of hypertensive patients with diabetes mellitus (19,20). Whereas diabetes mellitus is a compelling indication for use of RAS inhibitors (2), we found that CCBs are still commonly prescribed in this subgroup.…”
Section: Discussionmentioning
confidence: 89%
“…Reflecting the clinical evidence, including the findings of the ACCOMPLISH study [4], an angiotensin-receptor blocker (ARB) together with a calcium-channel blocker (CCB) is the combination most frequently prescribed to Japanese hypertensive patients [5,6]. For patients who have comorbidities such as hyperlipidemia, diabetes, and chronic renal disease, more aggressive treatment, with the addition of thiazide diuretics (i.e., hydrochlorothiazide or HCTZ) is provided to achieve therapeutic goals [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in Japan, CCBs are the most common followed by RAAS inhibitors (usually ARBs), while diuretics are commonly used in elderly patients [ 113 , 114 , 117 , 121 , 133 ]. The high use of CCBs in Japan was demonstrated in an analysis of pharmacies dispensing in Kitakyushu City (10,585 antihypertensive prescriptions) [ 113 ], a review of prescriptions dispensed at three Tokyo hospitals ( n = 27,033 without diabetes and n = 4604 with diabetes) [ 117 ] and two nationwide medical insurance claims analyses (one n = 59,867 [ 114 , 133 ] and the other n = 1,863,298 [ 121 ]).…”
Section: Resultsmentioning
confidence: 99%